2006
DOI: 10.1093/jnci/djj004
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune and Chronic Inflammatory Disorders and Risk of Non-Hodgkin Lymphoma by Subtype

Abstract: Our results confirm the associations between certain autoimmune disorders and risk of NHL and suggest that the associations may not be general but rather mediated through specific NHL subtypes. These NHL subtypes develop during postantigen exposure stages of lymphocyte differentiation, consistent with a role of antigenic drive in autoimmunity-related lymphomagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
286
1
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(329 citation statements)
references
References 55 publications
20
286
1
19
Order By: Relevance
“…While some studies suggest an increased risk of lymphoma in patients with psoriasis, [78][79][80][81][82][83][84][85][86] other studies do not support this association. [87][88][89][90][91][92][93][94][95][96][97] The largest study evaluating this association is a retrospective, population-based cohort study that enrolled 153,197 patients with psoriasis and 765,950 matched patients without psoriasis. 98 Patients were identified through the United Kingdom General Practice Research Database and analyses were age, gender and person-time adjusted.…”
Section: Malignanciesmentioning
confidence: 99%
“…While some studies suggest an increased risk of lymphoma in patients with psoriasis, [78][79][80][81][82][83][84][85][86] other studies do not support this association. [87][88][89][90][91][92][93][94][95][96][97] The largest study evaluating this association is a retrospective, population-based cohort study that enrolled 153,197 patients with psoriasis and 765,950 matched patients without psoriasis. 98 Patients were identified through the United Kingdom General Practice Research Database and analyses were age, gender and person-time adjusted.…”
Section: Malignanciesmentioning
confidence: 99%
“…513 Besides corroborating an association between risk of overall NHL and a history of RA (OR 5 1.5; 95% CI 1.1-1.9), primary Sj€ ogren's syndrome (OR 5 6.1; 95% CI 1.4-27), SLE (OR 5 4.6; 95% CI 1.1-22), and celiac disease (OR 5 2.1; 95% CI 1.0-4.8), this study demonstrated that some associations were more evident for certain NHL types. In particular, RA, Sj€ ogren's syndrome, SLE and celiac disease were associated with excess risk of diffuse large B-cell lymphoma (ORs ranging from 1.8 for RA to 11 for Sj€ ogren's syndrome); Sj€ ogren's syndrome was also associated with elevated risk of marginal zone lymphoma (OR 5 28); RA was associated with increased risk of lymphoplasmacytic lymphoma (OR 5 2.5); and celiac disease was associated positively with risk of T-cell lymphoma (OR 5 17).…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…543 Almost all B-cell lymphoproliferative disorders in solid organ and bone marrow transplant patients and in patients with congenital immune deficiencies are EBV-associated. 513,544,545 The risk of NHL is greater for patients who acquire EBV via transplantation from an EBV-positive donor; thus, the combined effects of acquiring a primary infection while immunosuppressed may augment risk. 523 EBV is causally linked to HL, 546 but a direct role of EBV in NHL etiology remains in question.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…Indeed, more than 10% of lymphoid neoplasms arise in the setting of an autoimmune diathesis ( 1,2 ). Prototypical examples of such an association include mucosa-associated lymphoid tissue (MALT) lymphomas of the salivary glands and enteropathy-associated T-cell lymphomas arising in patients with Sjogren's syndrome or celiac disease, respectively ( 2,3 ).…”
Section: Introductionmentioning
confidence: 99%